PENERAPAN MODEL PEMBELAJARAN THINK TALK WRITE (TTW) UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IIIA SDN 188 PEKANBARU - Titik Yuliani; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem of this research is the low skill of writing narration composition of student at IIIA grade SDN 188 Pekanbaru, from 37 students, students with very skilled category 2 students, students with skilled category 5 students, students with quite skilled category 15 students, students with less skilled category 15 students. The method used in this research is classroom action research, conducted in 2 cycles which aims to improve the skill of writing narration composition of student at IIIA grade SDN 188 Pekanbaru by applying the learning models think talk write (TTW) . The subjects of this study are student at IIIA grade SDN 188 Pekanbaru. Data obtained through observation and test. The results showed that the percentage of teacher activity in the first cycle of 72.22% with good category and cycle II increased to 83.33% with very good category. In addition, student activity on the first cycle of 72.22% with good category, in the second cycle increased to 83.33% with very good category. Meanwhile, the result of narration composition writing skill after applying of the learning models think talk write increased on UH1 with average 73,43 with big increase from base score 25,41% and mean UH II is 79,76 with big increase from score base of 36.22%. Based on the result of this research, it can be concluded that the application of the learning models think talk write (TTW) can improve narration composition writing skill of student at IIIA grade SDN 188 Pekanbaru.Key words: Think Talk Write, The narration composition writing skill